379 Contemporary use of guideline directed medical therapy in dilated cardiomyopathy: therapeutic optimization and prognostic benefits. (8th December 2021) - Venturelli, Francesco; Nuzzi, Vincenzo; Manca, Paolo; Santi, Giovanni; Barbati, Giulia; Gregorio, Caterina; Stolfo, Davide; Merlo, Marco; Sinagra, Gianfranco
Abstract: Aims: Therapy with antineurohormonal drugs at target doses has a prognostic benefits in heart failure with reduced ejection fraction. Dilated cardiomyopathy (DCM) represents a particular setting where the possible benefit of target doses of antineurohormonal drugs is unexplored. Methods and results: All patients enrolled from 1/1/1992 to 1/3/2020 in the Trieste Muscle Heart Disease register affected by DCM with data on the dosage of therapy available both enrollment and at follow-up visit (i.e., 6–12 month) were included. The population was divided according to the percentage of recommended dose prescribed (0–49%, 50–99%, 100%) of both renin-angiotensin system inhibitors (RASi) and beta blockers (BB). A composite of death/heart transplant/hospitalization for heart failure was considered as the primary endpoint; a composite of sudden cardiac death/major ventricular arrythmias/defibrillator intervention was evaluated as a secondary endpoint. Prognostic associations were explored with uni- and multivariate analyses, Cox regressions, Kaplan–Meier, cumulative incidence curves and propensity score matching. 826 patients were included. At baseline 789 (96%) were taking a RASi and 627 (76%) a BB. The target dose of RASi was prescribed in 29% and 36% of patients at enrolment and at follow-up visit, respectively. The percentage of patients taking the maximum recommended dose of BB was 10% at baseline and 17% after optimization. Predictors of reaching target dose for RASi were BMI < 25 kg/m 2, male sex [HR: 1.798 (95% CI: 1.073–3.012), P = 0.026] and higher systolic blood pressure [HR per mmHg 1.038 (95% CI: 1.025–1.051), P < 0.001]. Target dose predictors of BB were age [HR per year 0.527 (95% CI: 0.347–0.802), P = 0.003] and highest systolic blood pressure [HR per mmHg 1.024 (95% CI: 1.013–1.035), P < 0.001]. After adjustment target dose of RASi or BB did not show a significant association with the risk of primary outcome occurrence compared to those taking less than 50% ( P = 0.550 for RASi and P = 0.921 for BB). The incidence of arrhythmic events was significantly lower in patients taking 100% of recommended dose of BB compared to those taking less than 50% ( P = 0.009), after adjustment for confounders. The target dose of RASi was not associated with an arrhythmic events risk change ( P = 0.688). Conclusions: In DCM a significant number of patients do not tolerate maximal therapy doses, mainly due to hypotension. The achievement of the target dose of RASi and BB, after adjustment for confounders had a neutral effect on the incidence of heart failure-related events. Uptitration of BB to the recommended dose has a strong protective effect on arrhythmic events.